Analysis of High Frequency Intracranial Pressure Data in Neurocritical Care Patients: Insights into Normal Values and the Treatment Threshold. (16th November 2020) - Hawryluk, Gregory W.J; Neilson, Jessica; Huie, J. Russell; Zimmermann, Lara; Saigal, Rajiv; Ding, Quan; Hirschi, Ryan; Ferguson, Adam; Manley, Geoffrey T
Abstract: INTRODUCTION: Intracranial pressure (ICP) elevation is a compartment syndrome which impairs blood flow to the brain. Normal ICP values and the precise ICP threshold at which treatment should be initiated remain uncertain. METHODS: Our computer system prospectively and automatically collected q1 minute physiological data from ICU patients over a 6-year period. We studied data from 516 patients who underwent ICP monitoring, 372 of whom had a traumatic brain injury (TBI). Mean ICP was calculated, as was the proportion of ICP values above thresholds from 1–80mmHg in 1mmHg increments. The relationship between these measures and outcome was explored for various epochs up to 30d from the time of injury. A principal component analysis (PCA) was used to explore physiologic changes at various ICP thresholds and elastic net regression was used to identify ICP thresholds most predictive of Glasgow Outcome Scale score at discharge. RESULTS: A total of 4, 090, 964 q1 minute ICP measurements were recorded for the included patients (7.78 years of recordings). ICP values of 8–9mmHg were most commonly recorded and may reflect normal values. The PCA suggested state-shifts in the physiome occurred at intracranial pressures above 19mmHg and 24mmHg. Elastic net regression identified an ICP threshold of 19mmHg as most robust in predicting outcome when considering all neurocritical care patients, those with TBI as well as TBI patients who underwent craniectomy. ICP values above 19mmHg were associated with mortality while lower values were associated with survival. CONCLUSION: This study provides insight into what normal ICP values may be. An ICP threshold of 19mmHg was robustly associated with outcome in studied patients though lower ICP values correlated with outcome in surviving patients.